Influência do arcabouço hidroestratigráfico nas ocorrências de arsênio em águas subterrâneas ao longo do corredor termal do rio Uruguai (Argentina - Brasil - Uruguai) - Gastmans, Didier [UNESP]; Veroslavsky, Gerardo; Chang, Hung Kiang [UNESP]; Marmisolle, Josefina; Oleaga, Alejandro (My University, 2010)
The Thermal Corridor of Uruguay River is located in the triple border of Argentine, Brazil and Uruguay, and shows an intense economic thermal tourism activity, mainly based on groundwaters from Guarani Aquifer System (GAS). Recent studies have pointed out the occurrence of high concentrations of arsenic (>10 μg/L) in GAS groundwater in this area. The complex geological and hydrogeological framework in the area is associated to the Paraná Basin geological evolution south of the Assuncion-Rio Grande Arch; it encompass paleozoic marine sequences and continental sequences permian/eotriassic to mesozoic in age, which are covered by basaltic lavas of Serra Geral Formation. Iron oxide coatings have been described in sandstones of Buena Vista and Sanga do Cabral formations, which underlie GAS units. Arsenic occurrence is associated to sodium bicarbonate groundwater with pH values over 8.0. Arsenic is released to groundwater by desorption from iron oxides/hydroxides, as result of the higher pH of these waters, indicating that arsenic is released from the units that underlie GAS units. Increase in chromium and uranium concentrations are also related to high pH groundwaters, thus indicating special care on using groundwater from this region.

Localizado na fronteira entre Argentina, Brasil e Uruguai, o Corredor Termal do Rio Uruguai apresenta como principal atividade econômica o turismo termal, que se utiliza das águas do Sistema Aquífero Guarani (SAG). Estudos recentes vêm apontando a ocorrência de concentrações anômalas de arsênio nas águas do SAG nesta região. Os arcabouços geológico e hidrogeológico da área estão associados à evolução da Bacia do Paraná ao sul da Dorsal Assunção-Rio Grande, onde ocorrem sedimentos paleozóicos marinhos e sedimentos continentais permo-eotriássicos e mesozóicos, recobertos por lavas basálticas da Formação Serra Geral. Foram descritas ocorrências de coatings de óxidos de ferro recobrindo, principalmente, os grãos dos arenitos das Formações Buena Vista e Sanga do Cabral, unidades estas subjacentes ao SAG. As ocorrências de arsênio, identificadas na área, estão associadas a águas subterrâneas com pH superior a 8,0 e bicarbonatadas sódicas. O processo de desorção, a partir de arsênio adsorvido em óxidos e hidróxidos de Ferro, em função do elevado pH, é responsável pelas anomalias observadas, indicando que sua origem está associada aos arenitos das unidades subjacentes ao SAG. O aumento nas concentrações de cromo e urânio, também relacionado ao aumento de pH nas águas subterrâneas, aponta para a necessidade de cuidados especiais na utilização das águas subterrâneas da região. Palavras-chave: Sistema Aquífero Guarani, contaminação natural, arsênio, águas termais.
Oleaga - Influence of hydrostratigraphic framework in aresenic occurence in groundwater along the Uruguay River thermal corridor (Argentine-Brazil-Uruguay)
Keywords: Arsenic; Guarani aquifer system; Natural contamination; Thermal water; arsenic; basalt; bicarbonate; chromium; concentration (composition); geological survey; groundwater resource; hydrogeology; hydroxide; iron oxide; Mesozoic; Permian; pH; sodium; thermal regime; tourism development; uranium; Argentina; Brazil; Buena Vista County; Guarani Aquifer; Iowa; United States; Uruguay; Uruguay River; Sanga